PENGARUH PRODUKSI KELAPA SAWIT DAN TENAGA KERJA PADA PENDAPATAN USAHA TANAMAN KELAPA SAWIT DI PERUSAHAAN PERKEBUNAN SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI)TAHUN 2020-2023 - Tugiyarti, Siska; Haitamy, Eri Bestary Al; Saputra, Ferdyan Wana (Journal of Applied Accounting And Business, 2025)
This research aims to determine the influence of palm oil production and labor on business income in oil palm plantation companies listed on the Indonesia Stock Exchange in 2020-2023. The data used in this research is secondary data, namely data obtained from companies listed on the Indonesia Stock Exchange in 2020-2023. Data analysis uses quantitative data. Data analysis uses multiple linear regression methods. The results of this research are: 1) Palm oil production has no effect because the t test results obtained a significance value of 0.393; 2) Labor partially has an influence and is significant at 0.004; 3) Business income simultaneously has an effect because the calculated F test results are 6.915 and the F table is 3.28.